Analysis of Social Perception of the Tegaren Community on the Progress of Tourism Village - Joko Mijiarto; Rusdi Hidayat; Budi Prabowo; Firdaus Nuryananda; Praja Firdaus Nuryananda (Future Science, 2022)
This research is also a follow-up to the research with the same scheme in 2021, entitled